Research in economic anthropology. Vol. 21 (Emerald, 2002)
The general theme of Social Dimensions in the Economic Process is an old one in economic anthropology. On the abstract end it involves, first, the degree of social content of individual transactions and, second, how economic processes relate to social structure. More specifically, the theme relates to matters such as the need for trust resulting in personalized systems of economic transactions, and how institutions shape economic arrangements. In five parts, the first two parts deal with the social content and consequences of economic relations. Parts III and IV address particular institutions, the household and agrarian relations. The volume ends in Part V with chapters linked to globalization.
Keywords: Economic anthropology.; Economic history.; elektronické knihy; electronic books